2013
DOI: 10.1063/1.4830424
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel radio-frequency negative hydrogen ion source in conically converging configuration

Abstract: Volume-produced negative ion source still requires enhancement of current density with lower input RF (radio-frequency) power in lower operating pressure for various applications. To confirm recent observation of efficient negative ion production with a short cylindrical chamber with smaller effective plasma size, the RF-driven transformer-coupled plasma H(-) ion source at Seoul National University is modified by adopting a newly designed quartz RF window to reduce the chamber length. Experiments with the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the ion source group at Seoul National University (SNU) in Korea, a lot of research effort has been made towards the development of a volume production H − ion source based on radio-frequency (RF) transformer-coupled plasma (TCP) for long lifetime continuous wave (CW) operation [2][3][4][5][6]. Recently, we reported that the electron temperature in the driver region could be increased by just reducing the effective plasma size [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ion source group at Seoul National University (SNU) in Korea, a lot of research effort has been made towards the development of a volume production H − ion source based on radio-frequency (RF) transformer-coupled plasma (TCP) for long lifetime continuous wave (CW) operation [2][3][4][5][6]. Recently, we reported that the electron temperature in the driver region could be increased by just reducing the effective plasma size [3].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a lot of theoretical and experimental researches on this subject [8][9][10][11], the exact mechanism of magnetic filtering is still not fully understood. By adopting this conventional technique, we have tried to reduce the electron temperature at low pressure by strengthening the magnetic filter field near the extraction region [4,5]. Although we found some interesting features for the effect of filter field strength [5], the conventional technique has turned out to be not enough to reduce the electron temperature in the extraction region operating at the low pressure regime.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the electron temperature could be easily increased by shortening the length of the discharge chamber [7]. However, the overall increase of electron temperature failed to filter high energy electrons near the extraction hole efficiently [8]. Optimization of filter field strength depending on operating conditions were carried out to resolve this problem [9].…”
Section: Introductionmentioning
confidence: 97%